+0  
 
0
59
4
avatar

Am I correct or not please help ASAP. I can only yake this once . Thank you

 Dec 16, 2019
 #1
avatar+43 
+1

No, you are not correct. The correct answer is x=6.

 Dec 16, 2019
 #2
avatar+19789 
0

sqrt(2x-3) = x-3

2x-3 = (x-3)^2

2x-3 = x^2-6x+9

x^2-8x+12 = 0

(x-6)(x-2) = 0     so x = 2 or 6      Do both answers solve the equation?  Or is one of them extraneous?   What do YOU think?

 Dec 16, 2019
 #3
avatar
+1

there is only one answer i think

Guest Dec 16, 2019
 #4
avatar+19789 
0

Well, yes....there is only one.    Which one?   Substitute x = 2     and then x = 6 into the original equation to see which one works.

ElectricPavlov  Dec 16, 2019
edited by ElectricPavlov  Dec 16, 2019
edited by ElectricPavlov  Dec 16, 2019

8 Online Users

avatar